Evaluating digestate and raw manure in floral waste composting: physicochemical properties and microbiome dynamics - Kushwaha J.; Dhoble A.S. (My University, 2025)
Floral waste (FW) significantly contributes to landfill emissions, but composting emerges as a scientifically backed solution to counter this issue. This study delved into the promising potential of composting in managing FW, offering a crucial pathway to mitigate its environmental impact. Microbial diversity and dynamics in the FW composting were evaluated using anaerobic digester slurry (ADS) versus raw cow dung (CD) as inoculum. Significant increases in nitrate and phosphate concentrations were observed post-day 40, which might be attributed to the microbiome’s role in compost maturation. Bacillus increased significantly in CD compost (63.35%), while AD compost showed a minor increase (0.17%). Streptomyces increased in CD (129.5%) and AD (8.68%). FW composting promoted Haloarcula and Haloferax archaea, facilitating organic matter breakdown in high-salt environments while reducing methane-producing archaea, indicating aerobic conditions. Composting of CDFW demonstrated enhanced microbial species richness, whereas ADSFW exhibited greater microbial community diversity. This study demonstrates the enhanced utilization of ADS in composting floral waste, capitalizing on its diverse microflora. This integration enriches the compost, promotes the activity of key microorganisms for efficient organic matter degradation, and may contribute to the improvement of soil quality. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.